Formation of Political Party Images in Urban Village Communities as a Strategy Ahead of the 2024 General Elections - Isnaeni Qurotun Nisyak; Agus Machfud Fauzi (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2023)
ABSTRACTThe 2024 presidential election is the subject of much coverage in the mass media. Issues related to the pair of leaders who will run for office have been busy in various media today. There are many opportunities as well as challenges faced by various political parties ahead of the 2024 presidential election. Given the intense competition, political parties form a political image to attract the general public to support one of these parties. It was found that several political parties were also present directly to village communities in urban areas to find out what problems the community was facing. The purpose of this research is to see how political image is present in the life of urban village communities as part of the strategy ahead of the 2024 general elections. This study uses qualitative research methods with supporting data obtained from interviews and literature studies from news, journals, website, and others. The results of this study indicate that the political imagery carried out by several parties in urban village communities is to accommodate various kinds of aspirations and complaints of the community related to conditions, the economy, development, and others - Other. The formation of this political image can attract attention, especially in urban village communities to choose a suitable candidate. Political image is present as a form of strategy from political parties towards the 2024 general elections.Keywords: Political Image, Urban Village, ElectionÂ Â